The poetics of togetherness: Conviviality of asylum-seekers in the shadow of Hong Kong. (27th July 2022) - Cheng, Sealing
Abstract: This article examines the radical politics of a fragile togetherness on the margins of the state. A small but diverse group of long-term asylum-seekers found themselves in a decade-long limbo in Hong Kong, confronting an increasingly hostile border regime, and met regularly to 'do something as a group'. Despite the lack of any breakthrough and advice to break away as individual cases, they have persisted in staying 'as a group'. Drawing on participant observation with the group, Our Lives Matter, the article analyzes the ways these protracted asylum-seekers relate to each other as social beings, the mutuality and togetherness they cultivate, and the political possibilities opened up by such interconnections. Building on the scholarship of conviviality that examines 'togetherness-in-differnece', I develop the concept of poetics of togetherness to understand these asylum-seekers' conviviality as practice, ethics, and a method of being otherwise on the margins, invariably dialoguing with, disavowing, and defying the center. Could conviviality as ethical and political projects create radical alternatives? The poetics of togetherness recognizes the precarity and divisiveness on the margins, while attending to the power of sociality and interdependence, and emergent forms of engagement. The simultaneous making of social and political agents opens up alternative possibilities of being, relating, and acting in the shadow of state violence. We gain insights into the dynamics between 'margins' and 'center' by understanding these practices and ethics of communality as political and epistemic projects to challenge and possibly transform uneven power dynamics and exclusionary structures.